2011
DOI: 10.1007/s10151-011-0752-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis and carcinoid tumor in Meckel’s diverticulum. Three pathologies in one: a case report

Abstract: Incidental carcinoid tumor of the Meckel's diverticulum is an uncommon event. Herein, a case of a carcinoid tumor in Meckel's diverticulum that was incidentally found in a patient with acute appendicitis is presented. A 42-year-old Caucasian man presented with acute abdomen and clinical signs of acute appendicitis. A typical appendectomy was performed during which further abdominal exploration revealed a Meckel's diverticulum 60 cm proximal to the ileocecal valve, with an irregular and somewhat indurated seros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A number of reports in the literature describe NETs in a Meckel’s diverticulum that were discovered incidentally during an abdominal exploration for another indication or at autopsy[11,15,16,17]. A review of the literature by Nies et al[6] found that 64% of patients with NETs in a Meckel’s diverticulum were asymptomatic at the time of diagnosis, and 26% were found incidentally at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports in the literature describe NETs in a Meckel’s diverticulum that were discovered incidentally during an abdominal exploration for another indication or at autopsy[11,15,16,17]. A review of the literature by Nies et al[6] found that 64% of patients with NETs in a Meckel’s diverticulum were asymptomatic at the time of diagnosis, and 26% were found incidentally at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients with a MD associated NET is 55 years and the incidence is 2.5 times higher in men. 2,5 The five-year tumour specific survival rates range from 100% for stage I to 84.8% for stage IV. 5 In terms of NET grades, the survival rates are around 93.8% for low grade, 83.0% for intermediate grade and 50.0% for high grade tumours.…”
Section: Discussionmentioning
confidence: 99%
“…1 MD is a remnant from the incomplete obliteration of the vitelline duct during gestation; it is commonly asymptomatic and the average rate of complications being approximately 4%. 1,2 According to previous reports, diverticulectomy is the best option for complicated diverticula as well as the accepted treatment for incidental MD in the paediatric population. Prophylactic resection of asymptomatic diverticula discovered incidentally in adults remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…53 Carcinoid tumor associated with MD is usually diagnosed after bowel resection. 14,36,70,71 Moyana 54 found that jejunoileal carcinoid tumors most similarly resemble the type associated with MD, on immunohistochemical analysis. The survival rate for patients with locally-staged, small bowel carcinoid tumors in the absence of MD is approximately 75%.…”
Section: Malignancies Within MDmentioning
confidence: 97%